2015
DOI: 10.1016/j.ejphar.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ghrelin receptor-independent vascular actions of ulimorelin

Abstract: Ulimorelin (TZP101) is a ghrelin receptor agonist that stimulates intestinal motility, but also reduces blood pressure in rodents and humans and dilates blood vessels. It has been proposed as a treatment for intestinal motility disorders. Here we investigated the mechanisms through which ulimorelin affects vascular diameter. Actions of ulimorelin on wall tension of rodent arteries were investigated and compared with other ghrelin receptor agonists. Saphenous, mesenteric and basilar arteries were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In patients with diabetic gastroparesis, ulimorelin improved gastrointestinal symptoms such as vomiting and appetite loss, while there were no significant differences in improvement of gastrointestinal function between patients with POI taking ulimorelin and those taking placebo . Because of this insufficient efficacy and the risk of unexpected hypotension, its development for gastrointestinal indications has been discontinued …”
Section: Results Of Major Clinical Trials and Current Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with diabetic gastroparesis, ulimorelin improved gastrointestinal symptoms such as vomiting and appetite loss, while there were no significant differences in improvement of gastrointestinal function between patients with POI taking ulimorelin and those taking placebo . Because of this insufficient efficacy and the risk of unexpected hypotension, its development for gastrointestinal indications has been discontinued …”
Section: Results Of Major Clinical Trials and Current Statusmentioning
confidence: 99%
“…In a clinical trial to investigate the safety and efficacy of ulimorelin in patients with diabetic gastroparesis, defaecation was significantly increased as a side effect, supporting a therapeutic potential for impaired lower gastrointestinal function such as POI and chronic constipation . On the other hand, a recent study reported that ulimorelin could unexpectedly cause hypotension through the blockade of α 1 ‐adrenoceptors …”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ulimorelin is potent, gives long‐lasting effects on colorectal activity and appears to desensitize less than other compounds . However, this compound has off‐target effects at alpha receptors for catecholamines . Thus it is desirable to find other high potency stimulants of colorectal propulsion with limited desensitization.…”
Section: Introductionmentioning
confidence: 99%